Use of Modern Technology in Diagnostic and Treatment of Complications After Covid-19 in Cardiovascular System (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides insights into diseases of the cardiovascular system and diseases of the heart, arteries and veins. They are many and varied. Some of these diseases damage the heart, some arteries or veins, others damage the entire cardiovascular system. Arterial hypertension is one of the most common diseases of the cardiovascular system, and it is more common among older people. It is the main pathogenetic factor that often causes death or disability, such as myocardial infarction, stroke, heart failure.